KEEFEKTIFAN MODEL PEMBELAJARAN PROJECT BASED LEARNING BERBASIS KEARIFAN LOKAL KUDUS - Farida Hikmawati (COLLASE (Creative of Learning Students Elementary Education), 2023)
This study aims to analyze the effectiveness of the Project Based Learning model (PjBL) based on Kudus local wisdom for students' critical thinking skills. The type of research is experimental research. Data collection techniques with tests. The population in this study was the fourth-grade students of SDN 2 Karangmalang with 22 students and SDN 4 Rahtawu with 24 students. The PjBL learning model based on Kudus local wisdom is the treatment given to the experimental group and the control group is uses a conventional learning model. The results showed that the PjBL learning model based on Kudus local wisdom was effective to use. With an N-Gain value of 0.58 in the medium category and the results of the t-test, it was found that t count t table, namely 2.63 2.01537. Based on these results the PjBL learning model based on local wisdom for the critical thinking skills is effectively used.